Accounting For Development: Evaluating The Influence Of Accrual-Based Accounting And Governance On SDG 17 - Kaluku, Aditya D; Furqan, Andi Chairil; Betty, Betty (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study analyzes the influence of accrual-based accounting implementation and government governance quality on the achievement of Sustainable Development Goal 17 (SDG 17): Partnerships for the Goals. The data cover 153 countries during 2020–2023, obtained from reputable sources, including the Sustainable Development Report, the International Federation of Accountants (IFAC), and the World Bank. Using a panel linear regression approach with unbalanced data, the study examines the relationships between institutional, governance, and economic factors and the success of global partnerships. The findings indicate that both accrual-based accounting and government governance quality positively and significantly affect SDG 17 achievement, highlighting the importance of fiscal transparency, accountability, and institutional effectiveness in strengthening international partnerships. In contrast, differences in economic prosperity across countries do not appear to be a primary driver of global partnership success. These results underscore that institutional and governance factors are key to supporting sustainable development through cross-country collaborations. The main implication is that governments should prioritize institutional reforms, particularly the strengthening of accrual-based accounting systems, as a foundation for building trust, improving program effectiveness, and ensuring the sustainability of international cooperation within the 2030 Agenda framework.